(untitled) (International Journal of Rural and Urban Development, 2024)
The crucial role of communication in advancing knowledge and forging cooperation towards sustainable agricultural development cannot be emphasized enough. There has always been the need to connect farmers, agriculture industry experts and other stakeholders, and grant them access to veritable information and technical know-how. As a predominantly rural experience in many economies of the world, food and agricultural production require an orientation of the development of the rural populace through the dissemination of information and the introduction of an agricultural-related communication intervention. The quality of knowledge advancement and sustained agricultural development will depend on the quality of agricultural communication. Against the backdrop of identified gaps in the Nigerian experience of agricultural and rural communication, this study conducted a comparative analysis of a tabulation of conducted Rural Communication Studies (RCS) cases covering selected countries from South Asia, South East Asia as well as Pacific Island countries. It also reviewed other available secondary data on state of the art of Communication for Agricultural and Rural Development. Analysis of Rural Communication experience in the selected countries indicates that the selected countries are taking strategic approaches in their quest for rural development in combating poverty, and ensuring sustainability through more involvement of the people. Among salient discoveries from the study are that in many of the selected countries, strategic planning for agricultural and rural communication recognizes the critical place of food security, the management of natural resources, the crucial place and role of the people, as well as governance and institutions. A major implication for the identified gaps in Nigeria is the greater need to involve people as other stakeholders target audience at not only the formulation stages of the policy but also at the implementation stages, to enhance the communication imperatives of agricultural development.